Пространственное обучение и память белых крыс в водном лабиринте Морриса под влиянием биомассы штаммов стрептомицетов, выделенных из почв Республики Молдова - Гарбузняк, Анастасия; Шептицкий, Владимир; Бурцева, Светлана (Editura USM, 2024)
The aim of the work is to investigate the effect of long-term consumption of biomass of local strains of streptomycetes - Streptomyces massasporeus CNMN-Ac-06 and Streptomyces fradiae CNMN-Ac-11 on the spatial learning and memory in rats in the Morris water maze. It was found that biomass of strains Streptomyces massasporeus CNMN-Ac-06 and, to a greater extent, Streptomyces fradiae CNMN-Ac-11 leads to a noticeable decrease in such indicators, recorded during the training of animals in the Morris water maze, as the duration of the latent period of the animals the platform, the length of the path to the platform and the duration of the animal's stay in the non-target sectors of the maze, while the duration of the animals' stay in the target sector of the maze increased significantly. Thus, the biomass of studied local strains of streptomycetes contributes to the intensification of spatial orientation learning, improvement of working memory and the process of consolidation of spatial memory in rats, and these strains are promising for further research in order to isolate and identify substances with neuroprotective and nootropic properties.
Keywords: spatial learning and memory; working and long-term memory; Morris water maze; streptomycetes; biomass